2005
DOI: 10.1111/j.1601-0825.2005.01134.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐oral carcinomas in Maiduguri, north‐eastern Nigeria

Abstract: Squamous cell carcinoma was the most common oral carcinoma, commonly reported in the palate, among farmers and in the sixth decade of life. Its occurrence in under 40 year olds is three to six times greater than reported for the USA and Europe and may be associated with poor diet and the habitual use of kola nuts and tobacco. The survival rates of patients diagnosed with intra-oral carcinomas, although not available, would be expectedly low in view of the prognostic indicators recorded in this series. The rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 24 publications
1
31
2
Order By: Relevance
“…Also, most studies from Nigeria have shown oral cancer to be more prevalent in males than females [19,20,48,49]. However, Otoh et al [22] in Maiduguri North-east Nigeria found a male to female ratio of 3:4 and suggested that the relative higher preponderance of females in their study may be attributed to the increasing exposure of females in North-eastern Nigeria to carcinogens such as tobacco and alcohol. Other studies also reported female predilection for oral carcinomas [14,19].…”
Section: Sex Distribution Of Oral Cancercontrasting
confidence: 39%
See 3 more Smart Citations
“…Also, most studies from Nigeria have shown oral cancer to be more prevalent in males than females [19,20,48,49]. However, Otoh et al [22] in Maiduguri North-east Nigeria found a male to female ratio of 3:4 and suggested that the relative higher preponderance of females in their study may be attributed to the increasing exposure of females in North-eastern Nigeria to carcinogens such as tobacco and alcohol. Other studies also reported female predilection for oral carcinomas [14,19].…”
Section: Sex Distribution Of Oral Cancercontrasting
confidence: 39%
“…In Southsouth Nigeria, a study in University of Benin Teaching Hospital, [18] reported palate as the most common site for orofacial carcinomas. Similarly, Otoh et al [22] also reported the palate as the most common site of intraoral carcinomas in northern Nigerians. Some Nigerian studies from Ibadan, however, show that the tongue, palate and the mandibular alveolus are the sites most commonly affected with the floor of mouth and buccal mucosa being the least affected [20,51].…”
Section: Site Distribution Of Oral Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Irritation fibroma occurred in 14.4% of our samples which is similar to the 14.6% presented by Barker and Lucas, 33 but less than that found by Toida et al 24 Considering that irritation fibroma can be affected by oral habits, 34 which in turn are known to be related to social stress and cultural factors, this element may have a role in the differences observed between populations. Squamous cell carcinoma showed a prevalence of 13.8% in the current investigation which falls at the lower end of the 10.7 to 53% 27,[35][36][37] reported in other studies. There is a long list of items affecting the occurrence of squamous cell carcinoma ranging from the use of tobacco to phenolic agents and a number of systemic diseases 19 which can be responsible for these variations.…”
mentioning
confidence: 62%